A simple method for the design of cosine-modulated pseudo-QMF banks. (11th January 2011) - Kumar, A.; Singh, G.K.; Anand, R.S.
In this paper, a simple and efficient iterative technique for designing of Cosine-Modulated (CM) filter banks with approximate reconstruction is presented. In the proposed technique, cut-off frequency is optimised to satisfy a new Perfect Reconstruction (PR) condition at frequency (ω = π/2M). Different window functions have been used to design the prototype filter for CM filter banks. The simulation results illustrate the improvement achieved through this method over other existing methods in terms of amplitude distortion (eam ), Number of Iterations (NOI), aliasing distortion (ea ) and computation time (CPU time). When it is exploited for subband coding of the Electrocardiogram (ECG) and speech signals, the proposed method yields good fidelity performance measuring parameters.